Determination of pathogenicity novel mutations and their effects on g6pase protein function in Malaysian GSD1a patients / Amirah Assyiqqin Abd Rahman - Amirah Assyiqqin , Abd Rahman (2019)
Mutation in the glucose-6-phosphate catalytic subunit (G6PC) gene causes Glycogen Storage Disease (GSD) type Ia – a disease associated with glycogen metabolism deficiency. This condition is majorly characterized by hepatomegaly (enlargement of the liver), hepatosplenomegaly (enlargement of the spleen) and growth retardation which may advance to death if not treated early. The G6PC gene encodes for glucose-6-phosphatase (G6Pase) which is a key enzyme for the maintenance of glucose homeostasis in humans. GSDs are 100% penetrant and segregate in an autosomal recessive manner. Screening for mutations in the G6PC gene represents pre-emptive genetic screening and risk assessment efforts for individuals with problems of glycogen metabolism. Knowledge of the mutation spectrum that is prevalent in specific populations is essential to ensure precise diagnosis as well as the ensuing treatment strategies. This study aims to screen for pathogenic G6PC mutations in a set of Malaysian GSD Ia patients and to establish the local G6PC mutation spectrum. A total of 21 GSD Ia patients’ DNA were purified and each of the exon of the G6PC gene were amplified by Polymerase Chain Reaction (PCR). These were then subjected to DNA sequencing. A total of nine different mutations were detected: five mutations (c.648 G>T, c.248 G>A, c.706 T>A, c.664 G>A,c.518 T>C) have been reported previously while four are potentially novel mutations (c.155 A>T, c.226 A>T, c.337 C>T and c.1036 G>C). One single nucleotide polymorphism (SNP) was also detected from the screening. Three of the potentially novel mutations detected (c.155 A>T, c.337 C>T and c.1036 G>C) are missense mutation that change the original nucleotide to another while another mutation (c.226 A>T) is a nonsense mutation that creates a premature stop codon. The SNP detected in this study (c.547 A>G) has been previously reported in SNP databases. In order to determine the pathogenicity of the potentially novel mutations, restriction enzyme and TaqMan probe-based assays were designed to investigate its presence and allele frequency in a representative cohort of healthy individuals (n=50 Malays, n=50 Chinese, n=50 Indians). Restriction enzymes MseI and Mbo1 were used to screen forthe c.226 A>T mutation and c.337 C>T mutation respectively. For the other two mutations, c.155 A>T and c.337 C>T mutations, the TaqMan probe-based assayswere applied due to the inavailability of a restriction enzyme cutting site. Results obtained showed that no mutant allele was found in all 150 healthy individuals. In order to further confirm the pathogenicity of these potentially novel mutations, mutant alleles were constructed using site-directed mutagenesis (SDM) and transfected into mammalian cells for functional studies. However, functional studies were halted as satisfactory expression of the mutated protein was not achieved.